The Segmentation of the Academic Labour Market and Gender, Field, and Institutional Inequalities - Vohlídalová, Marta (Social Inclusion, 2021)
Using data from a 2017 survey of Czech academics this article examines the casualisation of working conditions in the Czech academic labour market (ALM) and explores gender, sectoral, and institutional inequalities through the lens of the theory of labour market segmentation. A hierarchical cluster analysis reveals three segments in the Czech ALM: core (40%), periphery (28%), and semi‐periphery (32%), which roughly align with work positions in the early, middle, and senior stages of an academic career. In the semi‐periphery gender is found to be a key factor in in determining working conditions, while in the periphery working conditions are most affected by the type of institution. In the core, gender differences are mainly reflected in the gender wage gap. The effects of casualisation on working conditions are found to be more pronounced in STEM fields than in the social sciences and humanities across the ALM, but wages are generally higher in STEM fields.